THE CORRELATION BETWEEN STUDENTS’ EMOTIONAL INTELLIGENCE AND READING COMPREHENSION ACHIEVEMENT - Dewi Septarani; Rekha Asmara; Dewi Sartika (Journal of English Education and Linguistics, 2021)
The objective of this report was to see if there was a correlation between emotional intelligence and reading comprehension achievement among eighth-grade students at SMPN 2 Kayuagung. A correlational research design was utilized. Purposive sampling was applied to choose 140 students for the study. A questionnaire was utilized to check students’ emotional intelligence and a writing test in the form of multiple choice about recount text was employed to measure students’ reading achievement. Before administering the test to the samples, the validity and reliability of the test were assessed on non-sample students at SMPN 2 Kayuagung. The Pearson Product Moment was used to examine the data. The correlation coefficient was found to be 0.240 based on the results at a p-value of 0.05. It was found that r-obtained (02.40) was higher than r-table (0.166). It meant students' emotional intelligence and reading comprehension had a positive relationship. Students who had good emotional intelligence had better reading achievement.